PERCEPTIONS OF STUDENTS MAJORING IN ACCOUNTING AT UNIVERSITY X TOWARDS THE ACCOUNTING LECTURER PROFESSION FROM THE PERSPECTIVE OF SOCIAL VALUES AND FINANCIAL MOTIVES - RASNI HANIPA USEMAHU; SHERLIE EVABIONI LATUAMURY (CV KULTURA DIGITAL MEDIA, 2022)
This research discusses the perceptions that exist within a student majoring in accounting towards accounting lecturers related to salary or financial rewards, and social values. The type of descriptive qualitative research that gives freedom to researchers to further develop their findings but still must be in accordance with the research boundaries. The object under study is students majoring in accounting who are currently studying a thesis as many as 30 students as has been described very clearly in the previous chapter. Based on the results of observations, questionnaires and interviews conducted by researchers related to the perceptions of students majoring in accounting towards accounting lecturers, it can be concluded that students do not agree if an accounting lecturer has a high starting salary and there are often salary increases, but they agree if an accounting lecturer has a pension fund, health benefits and old age